Reality Board / Muhammad Saufi Mustafar ... [et al.] - Mustafar, Muhammad Saufi; Jafri, Muhammad Syahrul Azhar; Alias, Luqman Hakim; Jemaain, Mohamad Izzami; Wan Ismail, Wan Musyirah (Universiti Teknologi MARA, Kedah, 2023)
"Reality Board" evokes the idea of creating and building wealth. It is an application that used the concept of a boarding game. This game has been created because nowadays there are a lot of issues that relate to the financial among the people especially in Malaysia. This can be seen where the high percentage of bankruptcy in early age, lower income employees that do not have financial planning, lack of knowledge about the importance of financial planning and more over. From the issues that stated, we know that people in Malaysia are lack of knowledge about financial planning and they spend their money without any goals to achieve. Hence, we created this game so that it can provide some information and knowledge on how they should plan their financial wisely without worrying to use their money. As benefits of this game, it can shows people how important of financial planning in life and promote people to make sure they can manage well their financial lifestyle. While the people enjoy the simple game then can earn the benefits of learning the concept of financial planning. As for our product, the idea of this game actually comes from the well-known game called “Monopoly”. We make some innovation based on the concept from Monopoly and turn into knowledgeable concept simulation on how to manage income, expenses and liabilities. The target market for our game are focusing on employees, university students and high school students. The reason why the employees is one of our target market is because most employees do not have the financial planning for their life and it makes their spending not depends on their income. We also focused on university and high school students because even though they may do not have any income yet, but they can start to learn and invest on how they should spend their money once they start to have their career.